Industrial machinery repair best maintenance practices pocket guide - Smith, Ricky (Butterworth-Heinemann, 2003)
This book addresses, in a simplistic manner, the proper principles and techniques for maintaining industrial equipment.
Keywords: Machinery -- Maintenance and repair.; Industrial equipment -- Maintenance and repair.; elektronické knihy; electronic books